5’UTR sequences influence protein levels in Escherichia coli by regulating translation initiation and mRNA stability - Chen, Fan; Cocaign-Bousquet, Muriel; Girbal, Laurence; Nouaille, Sébastien (Frontiers in Microbiology, 2022)
A set of 41 synthetic 5’UTRs with different theoretical translation initiation rates were generated to explore the role of 5’UTRs in the regulation of protein levels in Escherichia coli. The roles of the synthetic 5’UTRs in regulating the expression of different reporter genes were analyzed in vivo. Protein levels varied substantially between the different constructs but for most of the 5’UTRs, protein levels were not correlated with theoretical translation initiation rates. Large variations in mRNA concentrations were measured with the different 5’UTRs even though the same concentration of transcription inducer was used in each case. 5’UTRs were also found to strongly affect mRNA stability, and these changes in mRNA stability often contributed to observed differences in mRNA concentration. Unexpectedly, the effect of the 5’UTRs on mRNA half-lives was found to vary depending on the downstream reporter gene. These results clearly demonstrate that 5'UTRs contribute to gene expression regulation at the level of translation initiation and of mRNA stability, to an extent that depends on the nature of the downstream gene.